2013
DOI: 10.2174/1874836801307010193
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Design Procedure for Failure Mode Control of EB-Frames: Push-Over and IDA Analyses

Abstract: The paper is devoted to the investigation of the seismic response of eccentrically braced frames characterised by links having different length. In addition, the analysed structures have been designed according to a methodology, already proposed by the authors, aiming to guarantee a collapse mechanism of global type. Therefore, the results of the nonlinear analyses herein presented provide the validation of the proposed design procedure, by testifying that all the designed structures exhibit a global failure m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The aim of the non-linear dynamic analyses presented in this section is to check the collapse mechanism developed by the structures designed by P-TPMC [36]- [39]. In fact, it is expected that the percentage of structures exhibiting a collapse mechanism of global type completely developed or compatible with it agrees with the fixed probability given as design achievement of P-TPMC.…”
Section: Validation By Means Non-linear Dynamic Analysismentioning
confidence: 92%
“…The aim of the non-linear dynamic analyses presented in this section is to check the collapse mechanism developed by the structures designed by P-TPMC [36]- [39]. In fact, it is expected that the percentage of structures exhibiting a collapse mechanism of global type completely developed or compatible with it agrees with the fixed probability given as design achievement of P-TPMC.…”
Section: Validation By Means Non-linear Dynamic Analysismentioning
confidence: 92%
“…The work herein presented, developed in the contest of the RFCS Project EqualJoints Plus [23], aims at clarifying the role of joints on the design and performance of Dual-Eccentrically Braced Frames (D-EBFs) at the variation of prequalified steel beam-to-column joints typologies. To this scope, several D-EBFs have been designed by the Theory of Plastic Mechanism Control (TPMC) [24]- [35] which always allows the development of a collapse mechanism of global type.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to underline that, within structural reliability analysis and within the contest of failure mode control, the term "failure" denotes the attainment of a collapse mechanism different from the global one. In fact, many experimental investigations made by shaking table test [20]- [22] or Incremental Dynamic Analyses (IDA) [24]- [29] have shown that different failure mode can occur in structures under destructive earthquakes, and the reliability of having a collapse mechanism of global type sometimes is very low. Through the probabilistic procedure, it was possible to define an overstrength factor to apply to the deterministic version of TPMC with a given success probability, taking account the effects of random material variability.…”
Section: Introductionmentioning
confidence: 99%